(untitled) (Cardiovascular Journal, 2017)
Background: The superiority of the GRACE and TIMI risk scores in predicting the angiographic severity of coronary artery disease in patients with non ST-elevation myocardial infarction (NSTEMI) has not yet been established. This study was done to compare the GRACE and TIMI risk scores in predicting the angiographic severity of coronary artery disease in this group of patients. Method: The cross sectional study done in the Department of Cardiology, NICVD, Dhaka. The patients admitted with NSTEMI were evaluated to calculate the GRACE and TIMI risk score from April, 2015 to April, 2016.Coronary angiogram was done during index hospitalization and the severity of the coronary artery disease was assessed by vessel score and Gensini score. Results: Of 115 patients assessed, a positive correlation of the vessel score and Gensini score was observed with both the GRACE and TIMI risk scores (p=<0.001) and the GRACE score (r=0.59) correlated better than the TIMI score (r=0.52). The GRACE score presented area under the Receiver Operating Characteristic (ROC) curve of 0.844(95% CI = 0.774 0.914) significantly superior to the area under the ROC curve of 0.752(95% CI =0.658 0.846) of the TIMI score for the difference between the two scores. Conclusion: Both the GRACE and TIMI scores had good predictive value in predicting the severity of coronary artery disease in the patients with NSTEMI but when both the scores were compared, the GRACE score was found to be superior and correlated better with the severity of coronary artery disease. Cardiovasc. j. 2017; 10(1): 45-51